UPAYA PENCEGAHAN STUNTING MELALUI EDUKASI PRODUK OLAHAN IKAN KEPADA IBU PKK KECAMATAN TAHUNA - Tanod, Wendy Alexander; Rieuwpassa, Frets Jonas; Mahihody, Astri Juwita; Sambeka, Yana; Cahyono, Eko; Ansar, Novalina Maya Sari; Kasaluhe, Meityn Disye; Ijong, Frans Gruber; Karimela, Ely John; Makisake, Nadia Arlina; Somba, Vira Valentine; Biahimo, Syahputra (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This community partnership empowerment activity empowers mothers of the Family Welfare Development Team (TP. PKK) in Tahuna District, Sangihe Islands Regency, North Sulawesi through education on diversifying processed fish products to prevent stunting. This activity was carried out in September-October 2024 in three villages focused on handling stunting: Soataloara 1, Mahena, and Santiago, Tahuna District. The purpose of this empowerment activity is to empower the TP. PKK in diversifying processed fish products to help prevent stunting in the Sangihe Islands Regency. The methods used include hearings, initial observations, determining priority programs, facilitation and assistance, and monitoring and evaluation. Activities consisted of counseling on fish nutrition and technical guidance on making processed fish products such as meatballs, nuggets, and kaki naga. The evaluation was conducted through pre and post-tests to measure the improvement of participants' knowledge. The results showed a significant increase in the knowledge and skills of TP. PKK mothers. The average knowledge score on fish nutrition increased from 57% to 87%. As for the technical guidance on processed fish products, the skills improvement was seen in the making of meatballs (64% to 90%), nuggets (62% to 86%), and dragon feet (66% to 94%). This community partnership empowerment activity succeeded in increasing the understanding of PKK women in the Tahuna Sub-district about the importance of fish consumption in preventing stunting and improving the skills of TP. PKK mothers in processing fish into products with high nutritional value.